2021
DOI: 10.1186/s12917-021-02944-4
|View full text |Cite
|
Sign up to set email alerts
|

Cross-sectional study and genotyping of rotavirus-A infections in ruminants in Kuwait

Abstract: Background Group A rotaviruses (RVA) are zoonotic pathogens responsible for acute enteritis in human and neonatal ruminants. This research aimed to determine the prevalence of RVA in ruminants (cattle, sheep, and goats) and investigate the circulating RVA genotypes in these animals in Kuwait. We conducted a cross-sectional study to detect RVA in ruminants, using an immunochromatography test (IC), direct sandwich ELISA test, and real-time RT-PCR (RT-qPCR) assay using fecal samples. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 41 publications
0
2
0
2
Order By: Relevance
“…(26.9%), bovine astrovirus (22.4%), Rotavirus (11.1%), Salmonella enterica (2.6%), or Escherichia coli (1.8%). In another investigation, Abdou et al 30 discovered that the prevalence of Group A rotaviruses in non-diarrheic cattle, sheep, and goats was 2.9%, 1.3%, and 2.8%, respectively. Zhong et al 32 provided a possibly more dramatic example when they showed that the relative prevalence of potentially pathogenic bacteria, like Bacteroides, in healthy lambs was more than double that in diarrhoeic pen mates using 16S rRNA sequencing of the gut microbiota .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…(26.9%), bovine astrovirus (22.4%), Rotavirus (11.1%), Salmonella enterica (2.6%), or Escherichia coli (1.8%). In another investigation, Abdou et al 30 discovered that the prevalence of Group A rotaviruses in non-diarrheic cattle, sheep, and goats was 2.9%, 1.3%, and 2.8%, respectively. Zhong et al 32 provided a possibly more dramatic example when they showed that the relative prevalence of potentially pathogenic bacteria, like Bacteroides, in healthy lambs was more than double that in diarrhoeic pen mates using 16S rRNA sequencing of the gut microbiota .…”
Section: Discussionmentioning
confidence: 99%
“…To date, no study has delved into this aspect, leaving a signi cant gap in our understanding of neonatal diarrhea in farm animals. Nevertheless, intriguing observations have been made indicating that despite carrying enteric pathogens, many neonatal animals exhibit no clinical signs of diarrhea 30,31,32 .…”
Section: Introductionmentioning
confidence: 99%
“…Daha az yaygın olarak G8 genotipi de tespit edilmiştir 16 . Bu genotipler genellikle P [5], P [11] genotipleri ve daha az sıklıkla P [1] genotipi ile ilişkilendirilmiştir 17 . Türkiye' de ishalli buzağılarla yapılan saha çalışmalarda sıklıkla G10P [11] genotipine rastlanmaktadır 11 .…”
Section: Tartışma Ve Sonuçunclassified
“…Saha çalışmaları sırasında tespit edilen sığır rotavirus genotiplerinin büyük çoğunluğu G6, G10 11 ve daha az yaygın olan G8 olarak tespit edilmiştir 16 . Bu genotipler genellikle P [5], P [11] ve daha az sıklıkla P [1] ile ilişkilendirilmiştir 17 .…”
Section: Introductionunclassified